Requirements for the teacher-therapist of persons with autism spectrum disorder – challenges for the new specialisation - Buława-Halasz, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Joanna Buława-Halasz, Requirements for the teacher-therapist of persons with autism spectrum disorder – challenges for the new specialisation. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 335–349. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/ 10.14746/ikps.2019.27.15 The text concerns the introduced standards for educating teachers-therapists of persons with autism spectrum disorder. This new specialisation in special pedagogy is meant to respond to the needs of autistic people, but its form is not fully responsive to real needs in this area.